A magnesium-based high-temperature resistant filler for rubber conveyor belts and a method for producing the same

CN121378890BActive Publication Date: 2026-09-04GUANGXI WUXUAN HUAHENG MINING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511669399.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-14
Publication Date
2026-09-04
Estimated Expiration
2045-11-14

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种用于橡胶传送带的镁基耐高温填料及其制备方法,通过植酸镁包覆层提升填料的热稳定性和阻燃性,利用钛酸酯偶联剂实现填料与橡胶基体的界面结合力,并借助云母粉协同强化力学性能和耐久性,有效解决了传统水镁石填料在高温下易分解、与橡胶相容性差的关键技术难题,显著提升了橡胶传送带在冶金、矿山等高温工况下的耐久性和使用寿命

Benefits of technology

1、本发明通过构建植酸镁包覆水镁石、钛酸酯偶联界面及硅烷改性云母粉复配的三元协同体系,系统解决了传统水镁石填料热稳定性差、与橡胶界面相容性弱以及补强效果单一的问题。该体系从填料本体改性、界面强化到多维网络构建层层递进,显著提升了橡胶传送带在高温、高磨损工况下的综合耐久性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a magnesium-based high-temperature-resistant filler for rubber conveyor belts and a preparation method thereof, and belongs to the technical field of rubber fillers. Magnesium phytate is in-situ deposited on the surface of brucite through a coprecipitation method to obtain magnesium phytate-brucite composite powder. A titanate coupling agent is uniformly grafted to the surface of the composite powder by using a spraying process. Finally, the titanate-treated composite powder is mechanically mixed with silane-modified mica powder at a high speed to obtain the magnesium-based high-temperature-resistant filler for rubber conveyor belts. The application improves the thermal stability and flame retardance of the filler through the magnesium phytate coating layer, realizes the interfacial bonding force between the filler and the rubber matrix by using the titanate coupling agent, and strengthens the mechanical properties and durability by means of the mica powder. The application effectively solves the key technical problems that the traditional brucite filler is easy to decompose at high temperatures and has poor compatibility with rubber, and significantly improves the durability and service life of the rubber conveyor belt under high-temperature working conditions such as metallurgy and mining.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of rubber filler technology, specifically a magnesium-based high-temperature resistant filler for rubber conveyor belts and its preparation method. Background Technology

[0002] Rubber conveyor belts operate under extreme conditions in metallurgy, mining, and chemical industries for extended periods, requiring excellent resistance to high and low temperatures, mechanical strength, and aging resistance. To improve the overall performance of the rubber matrix and control costs, functional fillers are typically added. Fillers not only increase volume and reduce production costs, but more importantly, they improve the mechanical properties of rubber through particle reinforcement. Their interfacial compatibility with rubber molecules directly affects the final service life of the conveyor belt.

[0003] Currently, the commonly used fillers for rubber conveyor belts are mainly calcium carbonate, carbon black, and talc. Among them, calcium carbonate is widely used because the raw materials are readily available and the price is low. However, calcium carbonate filler itself has prominent shortcomings. It has poor high temperature resistance and is prone to interface cracking due to thermal decomposition at high temperatures. It also has weak acid and alkali resistance and is prone to corrosion in chemical conveying scenarios, which affects the overall structural stability of the conveyor belt.

[0004] As a magnesium-based filler with great potential, brucite has received increasing attention in the rubber industry in recent years. Compared with traditional calcium carbonate fillers, brucite has a variety of unique properties, especially its excellent high-temperature resistance and flame retardant properties, which makes it show great promise for the high-performance of rubber conveyor belts. In addition, brucite can be synthesized from the abundant local dolomite resources through processes such as calcination, hydration, and separation. This preparation route provides a raw material basis for its sustainable supply.

[0005] However, magnesia filler is prone to early thermal decomposition during the processing of rubber conveyor belts and under high-temperature conditions. This not only weakens the flame retardancy but also damages the long-term mechanical properties of the material due to the loose structure of the decomposition products. At the same time, the surface of magnesia filler is highly hydrophilic and has poor compatibility with the hydrophobic rubber matrix, which easily leads to difficulties in mixing and dispersion and weak interfacial bonding. This not only deteriorates the processing performance but also accelerates the aging of the material. These problems make it difficult to meet the requirements of industrial conveying scenarios with high requirements for dynamic mechanical properties and long-term durability. Summary of the Invention

[0006] The purpose of this invention is to provide a magnesium-based high-temperature resistant filler for rubber conveyor belts and its preparation method. The thermal stability and flame retardancy of the filler are improved by a magnesium phytate coating layer, the interfacial bonding force between the filler and the rubber matrix is ​​achieved by using a titanate coupling agent, and the mechanical properties and durability are enhanced by the synergistic effect of mica powder. This invention effectively solves the key technical problems of traditional brucite fillers being easy to decompose at high temperatures and having poor compatibility with rubber, and significantly improves the durability and service life of rubber conveyor belts under high-temperature conditions such as metallurgy and mining.

[0007] The objective of this invention can be achieved through the following technical solutions: A method for preparing a magnesium-based high-temperature resistant filler for rubber conveyor belts includes the following steps: Step 1: Using the co-precipitation method, with brucite powder as the matrix core, phytic acid as the organic phosphorus source, and magnesium chloride as the magnesium source, magnesium phytate is uniformly coated by in-situ deposition to obtain magnesium phytate@brucite composite powder.

[0008] Step 2: Using TTS-toluene solution as a modifier, titanate coupling agent molecules are chemically bonded to the surface of magnesium phytate@brucite composite powder to obtain titanate-esterified magnesium phytate@brucite composite powder.

[0009] Step 3: The titanate-modified magnesium phytate@magnesium hydroxide composite powder is mixed with silane-modified mica powder by high-speed mechanical mixing to obtain magnesium-based high-temperature resistant filler for rubber conveyor belts.

[0010] Furthermore, the specific preparation steps for the magnesium-based high-temperature resistant filler used in rubber conveyor belts are as follows: Titanate-modified magnesium phytate@magnesium hydroxide composite powder and silane-modified mica powder were placed in a high-speed mixer and mixed at 500-800 r / min for 10-15 min at room temperature. Then, the mixture was mixed at 1000-1500 r / min for 15-25 min. The mixture was then dried in an air-drying environment at 75-85℃ for 1-2 h. Finally, it was passed through a 150-200 mesh sieve to obtain magnesium-based high-temperature resistant filler for rubber conveyor belts.

[0011] Furthermore, the mass ratio of titanate-esterified magnesium phytate@magnesium hydroxide composite powder to silane-modified mica powder is 50-70g:3-6g.

[0012] Furthermore, the specific preparation steps of the titanate-esterified magnesium phytate@brucite composite powder are as follows: Tristearoyloxyisopropyl titanate was dissolved in toluene and stirred until completely dissolved to prepare a coupling agent solution, which was then transferred to a sprayer for later use. Magnesium phytate@brucite composite powder was added to a reaction vessel and preheated and stirred at 65-75℃ and 200-400 r / min for 20-30 min. The coupling agent solution was then slowly and evenly sprayed into the reaction vessel through a sprayer. After spraying, the reaction vessel was sealed and reacted at 300-500 r / min and 65-75℃ for 50-70 min. After the reaction was completed, the powder product was vacuum dried at 75-85℃ for 2-3 h to finally obtain titanate-esterified magnesium phytate@brucite composite powder.

[0013] Furthermore, the ratio of the amount of tristearoyloxyisopropyl titanate, toluene, magnesium phytate@brucite composite powder is 1.5-2.4g: 20-30mL: 50-70g.

[0014] Furthermore, the specific preparation steps of the magnesium phytate@brucite composite powder are as follows: A 58.7% phytic acid solution was added to a reaction vessel, and a 5-10% ammonia solution was slowly added dropwise to adjust the pH of the system to 6.5-7.5. A magnesium hydroxide suspension was then added to the reaction vessel, and the mixture was stirred at 300-600 r / min at room temperature. Magnesium chloride solution was then slowly added dropwise to the reaction vessel at a rate of 1-2 drops / s. The mixture was stirred at a constant temperature for 1-1.5 h. After the reaction was completed, the product was washed with deionized water until the filtrate was neutral. The product was then filtered, and the filter cake was dried at 75-85℃ for 4-6 h. Finally, the dried block product was ground and passed through a 150-200 mesh standard sieve to obtain magnesium phytate@magnesium hydroxide composite powder.

[0015] Furthermore, the brucite suspension is prepared by stirring 80-120g of brucite powder and 1-2.5L of deionized water at room temperature at a speed of 200-500r / min for 10-30min.

[0016] Furthermore, the magnesium chloride solution consists of 14-26g of magnesium chloride hexahydrate and 80-150mL of deionized water.

[0017] Furthermore, the mass ratio of brucite powder, magnesium chloride hexahydrate, and phytic acid compounds is 80-120g: 14-26g: 16-22g.

[0018] The beneficial effects of this invention are: 1. This invention systematically solves the problems of poor thermal stability, weak compatibility with rubber interfaces, and limited reinforcement effect of traditional brucite fillers by constructing a ternary synergistic system of magnesium phytate-coated brucite, titanate coupling interface, and silane-modified mica powder. This system progressively improves the overall durability of rubber conveyor belts under high-temperature and high-wear conditions through layer-by-layer modification of the filler body, interface strengthening, and multi-dimensional network construction.

[0019] 2. In this invention, the magnesium phytate@brucite core-shell structure effectively inhibits the early decomposition of brucite during processing and at high temperatures through a dense coating layer, thereby improving thermal stability and flame retardancy. As a rigid organic-inorganic hybrid layer, this coating layer can effectively transfer and disperse stress, directly contributing to the reinforcing effect of the filler and improving the mechanical properties of the matrix. The polar functional groups such as phosphate groups enriched on its surface not only provide a strong reaction anchor for the titanate coupling agent, but also fundamentally improve the initial affinity with the rubber matrix, creating an excellent transition interface for subsequent coupling agent modification.

[0020] 3. The surface modification process of the titanate coupling agent used in this invention achieves uniform dispersion and chemical grafting of the coupling agent on the filler surface through spraying. The titanium hydroxyl groups generated by hydrolysis form stable Ti-OP coordination bonds and Ti-O-Mg chemical bonds with the phosphate groups and residual hydroxyl groups on the filler surface. This double bonding firmly anchors the coupling agent molecules to the filler surface, effectively strengthening the interfacial bonding. The organic hydrophobic layer constructed by the long-chain alkyl group of the coupling agent significantly reduces the surface energy of the filler, greatly improving its compatibility with the hydrophobic rubber matrix, fundamentally solving the core problems of difficult mixing and dispersion and weak interfacial bonding. The modified filler surface becomes smooth, effectively reducing stress concentration and avoiding mechanical damage to the rubber molecular chains by sharp edges, thereby synergistically enhancing the tear resistance and wear resistance of the composite material. Finally, a strong and tough interface is formed between the filler and the rubber, realizing efficient stress transfer and comprehensively improving the mechanical properties and durability of the rubber conveyor belt under dynamic load.

[0021] 4. This invention further optimizes the interfacial characteristics and reinforcing structure of the composite filler by introducing silane-modified mica powder as a synergistic reinforcing component. The long alkyl chains on its surface have excellent affinity with the hydrophobic layer on the surface of the titanate-modified main filler. During high-speed mechanical mixing, the two are entangled through intermolecular forces in the surface organic layers, achieving a dual reinforcing mechanism of hydrophobic synergy and structural complementarity. This not only promotes the uniform dispersion of mica powder in the system and avoids agglomeration, but also fully utilizes the barrier effect of its layered structure, effectively delaying the diffusion of heat and oxygen and extending the stress transmission path. Together with the main filler, it forms a multi-dimensional reinforcing network that combines rigidity and flexibility, thereby synergistically improving the tear strength, abrasion resistance, and heat and oxygen aging resistance of the composite material. This results in the final rubber conveyor belt cover rubber maintaining excellent mechanical strength while possessing significantly improved long-term durability. Detailed Implementation

[0022] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0023] Example 1: A method for preparing a magnesium-based high-temperature resistant filler for rubber conveyor belts S1: Mix 100g of dried brucite powder with 1.5L of deionized water and stir at 350r / min for 20min at room temperature to obtain a brucite suspension; separately weigh 14.5g of magnesium chloride hexahydrate and dissolve it in 115mL of deionized water to obtain a magnesium chloride solution.

[0024] Add 20g of 58.7% phytic acid solution to the reactor, slowly add 5-10% ammonia water to the reactor to adjust the pH of the system to 7, add the magnesium chloride suspension to the reactor, stir at 450 r / min at room temperature, and then slowly add the above magnesium chloride solution to the reactor at a rate of 1-2 drops / s. Stir the reaction at a constant temperature for 1 hour. After the reaction is completed, wash the product with deionized water until the washing filtrate is neutral, filter, and dry the filter cake at 80℃ for 5 hours. Finally, grind the dried block product and pass it through a 200-mesh standard sieve to obtain magnesium phytate@magnesium chloride composite powder.

[0025] Using a co-precipitation method, with brucite powder as the matrix core, phytic acid as the organic phosphorus source, and magnesium chloride as the magnesium source, in a weakly neutral reaction environment regulated by ammonia water, the phosphate groups in the phytic acid molecules undergo a coordination reaction with magnesium ions to generate magnesium phytate, which is insoluble in water. By slowly adding magnesium chloride solution and continuously stirring, magnesium phytate can be deposited in situ and uniformly coated on the surface with brucite particles as nucleation sites, ultimately forming a magnesium phytate@brucite composite powder with brucite as the core and magnesium phytate as the shell.

[0026] S2: Dissolve 2g of titanate coupling agent tristearoyloxyisopropyl titanate (TTS) in 25mL of toluene solvent and stir until completely dissolved to obtain a coupling agent solution. Transfer the solution to a sprayer for later use. Add 60g of magnesium phytate@brucite composite powder to the reactor and preheat and stir for 25min at 70℃ and 300r / min to loosen the filler powder. Maintain the temperature and stirring state in the reactor. Slowly and evenly spray the coupling agent solution into the reactor through the sprayer. After spraying, seal the reactor and react for 60min at 400r / min and 70℃. After the reaction, vacuum dry the powder product at 80℃ for 2.5h to completely remove the toluene solvent, and finally obtain titanate-esterified magnesium phytate@brucite composite powder.

[0027] Using chemical grafting technology, magnesium phytate@brucite composite powder is used as the matrix, and a toluene solution of tristearoyloxyisopropyl titanate (TTS) is used as the modifier. The coupling agent solution is uniformly dispersed on the surface of the filler in a closed reactor at 70°C by spraying. The isopropoxy group of the titanate molecule is hydrolyzed to generate titanium hydroxyl group under the action of trace moisture in the system. The unreacted phosphate group in the phytate molecule undergoes coordination to form a stable Ti-OP coordination bond. At the same time, the titanium hydroxyl group also undergoes a condensation reaction with the hydroxyl group remaining on the surface of brucite to form a Ti-O-Mg covalent bond. The two bonding methods work together to firmly anchor the titanate molecule to the surface of the composite powder. Its long-chain stearyloxy group constructs an organic interface layer, and finally, a titanate-esterified magnesium phytate@brucite composite powder with organic surface and excellent hydrophobicity and rubber compatibility is obtained.

[0028] S3: Mix 0.18g hexadecyltrimethoxysilane, 1.8g anhydrous ethanol and 0.18g deionized water, and hydrolyze in a water bath at 60℃ for 50min to obtain silane hydrolysate. Add 9g dried mica powder and 45mL deionized water to a reaction vessel and ultrasonically disperse for 30min to prepare a uniform slurry. Slowly add 2.16g silane hydrolysate dropwise to the vessel and react at 65℃ and 400r / min for 2.5h. After the reaction, filter the product and wash with ethanol and deionized water to remove physically adsorbed silane. Finally, vacuum dry at 80℃ to constant weight to obtain silane-modified mica powder.

[0029] A wet modification process is employed, in which hexadecyltrimethoxysilane is hydrolyzed in an ethanol-water mixture by heating in a water bath. Its methoxy group is converted into highly reactive silanol groups. Subsequently, under heating and stirring conditions, these silanol groups undergo a dehydration condensation reaction with the hydroxyl groups inherent on the surface of mica powder to form strong Si-O-Si covalent bonds, anchoring the silane molecules to the mica surface. At the same time, the long hexadecyl chain at the other end of the silane extends outward, thereby constructing an organic molecular layer on the surface of the mica powder particles.

[0030] S4: Place 60g of titanate-modified magnesium phytate@magnesium hydroxide composite powder and 4.5g of silane-modified mica powder in a high-speed mixer. First, mix at room temperature at 650r / min for 12min to initially mix the two fillers. Then, increase the speed to 1200r / min and continue mixing for 20min. Next, ventilate and dry the mixture at 80℃ for 1.5h to remove adsorbed ambient moisture and promote the entanglement of the organic layers on the surfaces of the two fillers through intermolecular forces. Finally, pass the mixture through a 200-mesh sieve to obtain magnesium-based high-temperature resistant filler for rubber conveyor belts.

[0031] Examples 2-4: A method for preparing magnesium-based high-temperature resistant filler for rubber conveyor belts. The difference from Example 1 is that the molar ratio of phytic acid to magnesium chloride is changed by adjusting the amount of brucite, phytic acid and magnesium chloride added in step S1 to study the effect of the stoichiometric composition of the magnesium phytate coating on the final performance. The remaining steps and parameters remain the same. The specific addition amounts are shown in Table 1 below.

[0032] Table 1. Comparison of the amount of substances used in step S1 Example 5: A method for preparing a magnesium-based high-temperature resistant filler for rubber conveyor belts, the difference from Example 1 is that the hexadecyltrimethoxysilane in step S3 is replaced with an equimolar amount of octadecyltrimethoxysilane, while the remaining steps and parameters remain the same.

[0033] The raw materials used in Examples 1-6 of this application are all commercially available. Among them, brucite was purchased from Haicheng Jinghua Micro Powder Factory; phytic acid was purchased from Guangzhou Suixin Chemical Co., Ltd.; magnesium chloride hexahydrate, ammonia and toluene were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; tristearate isopropyl titanate (TTS) was purchased from Hubei Dali Chemical Co., Ltd.; and mica powder was purchased from Jiangxi Kete Fine Powder Co., Ltd.

[0034] Comparative Example 1: Based on Example 1, steps S1 and S2 were omitted, and the titanate phytate magnesium@brucite composite powder in step S4 was replaced with 60g of unmodified brucite powder that had only passed through a 200-mesh standard sieve. The remaining steps and parameters remained unchanged, and magnesium-based high-temperature resistant filler was obtained.

[0035] Comparative Example 2: Based on Example 1, step S2 was omitted, and the titanate phytate magnesium@brucite composite powder in step S4 was replaced with phytate magnesium@brucite composite powder prepared only in step S1. The remaining steps and parameters remained unchanged, and magnesium-based high-temperature resistant filler was obtained.

[0036] Comparative Example 3: Based on Example 1, in step S4, silane-modified mica powder was not added. Instead, 60g of titanate-modified magnesium phytate@magnesium hydroxide composite powder was mixed and treated under the same conditions. The remaining steps and parameters remained unchanged to obtain magnesium-based high-temperature resistant filler.

[0037] Comparative Example 4: Based on Example 1, step S1 was omitted, and titanate modification in step S2 was performed directly with magnesia powder, while the remaining steps and parameters remained unchanged, to obtain magnesium-based high-temperature resistant filler.

[0038] The magnesium-based high-temperature resistant fillers prepared in Examples 1-6 and Comparative Examples 1-4 were used to prepare rubber conveyor belt cover adhesives and their performance was tested. The specific preparation steps are as follows: In an internal mixer with an initial temperature of 50°C, 100 parts of natural rubber are plasticized for 20 seconds, then 50 parts of filler, 5 parts of plasticizer, 3 parts of antioxidant and 3 parts of activator are added for master mixing. When the temperature rises to 120°C, the rubber is discharged. Then, the resulting master rubber is put back into the internal mixer, and after 20 seconds, a vulcanizing agent is added for final mixing. The rubber is discharged at 110°C. Finally, the final rubber is vulcanized on a flat vulcanizing machine at 150°C and 10MPa pressure to obtain the rubber conveyor belt cover rubber.

[0039] The performance of the rubber conveyor belt cover rubbers prepared in Examples 1-6 and Comparative Examples 1-4 was tested. Hardness was determined according to the method specified in ASTM D2240-2010, using 6mm thick specimens, and the material's resistance to indentation was measured on a Shore A hardness tester. Tensile strength and elongation at break were determined according to the method specified in ASTM D412-2006, using dumbbell-shaped type 1 specimens, and the tests were completed at room temperature and a tensile speed of 500mm / min. Tear strength was determined according to ASTM... The tear propagation resistance of the material was determined using the method specified in standard D624-2007, employing right-angled specimens and under the same tensile speed. The limiting oxygen index was determined according to the method specified in standard GB / T10707-2008, using 80mm×10mm×4mm test strips. The minimum oxygen concentration required for the material to sustain combustion was measured in an oxygen index meter to evaluate flame retardant performance. Abrasion loss was determined according to the method specified in standard GB / T9867-2008, using a rotary roller abrasion tester to measure the volume loss of the specimen after friction, characterizing abrasion resistance. Thermogravimetric analysis (TGA) was determined according to the method specified in standard GB / T27761-2011, using a specimen with a mass of approximately 10mg. The temperature was programmed to rise from room temperature to 800℃ at a rate of 10℃ / min in a nitrogen atmosphere in a thermogravimetric analyzer. The thermal stability was evaluated by measuring the temperature at which 5% weight loss occurred (T5%); a higher T5% indicates better thermal stability. The test results are shown in Table 3. Table 2 Performance test results of the cover rubber of each rubber conveyor belt As can be seen from the test results in Table 2, Examples 1-6 adopted a synergistic modification system consisting of magnesium phytate-coated brucite core-shell structure, titanate coupling surface modification, and mica powder compounding. The core-shell structure was constructed by co-precipitation method, and the coupling agent was uniformly dispersed and the organic layer was entangled by spraying method. In the end, the heat resistance, interfacial compatibility and mechanical strength of magnesium-based filler were synergistically improved.

[0040] Examples 2-4 adjust the molar ratio of phytic acid to magnesium chloride in step S1 to control the chemical state and surface properties of the magnesium phytate coating. In Example 2, when the molar ratio of magnesium ions to phytic acid is 3:1, a large number of phosphate groups in the phytic acid molecules do not participate in the reaction, providing abundant reaction sites for the subsequent titanate coupling agent, thus constructing a strong and tough interfacial layer. This gives the filler the best compatibility and stress transfer efficiency in the rubber matrix, exhibiting the highest tensile strength, elongation at break, and excellent wear resistance. However, this sacrifices the integrity of the coating, resulting in relatively low thermal stability and limiting oxygen index. Conversely, Example 4 uses a high molar ratio, forming a dense and complete coating, exhibiting optimal thermal stability and flame retardancy. However, due to insufficient surface active sites, its mechanical properties and wear resistance are weakened. Examples 1 and 3 achieve the best balance between interfacial bonding and thermal protection performance by using a moderate molar ratio, thus enabling the rubber conveyor belt cover rubber to obtain balanced and excellent comprehensive durability.

[0041] Example 5 replaced hexadecylsilane with octadecylsilane, and its tear strength and abrasion resistance were comparable to those of Example 1, indicating that silanes with longer alkyl chains can further improve the protective effect by enhancing the hydrophobicity of the interface.

[0042] The tensile strength, tear strength, and abrasion resistance of the sample in Comparative Example 1 were the worst among all groups, and its limiting oxygen index and initial decomposition temperature were also the lowest. This may be because the coating and coupling processes in steps S1 and S2 were completely omitted, and unmodified brucite filler was used directly. On the one hand, the lack of a magnesium phytate coating layer led to the early decomposition of brucite at high temperatures, resulting in deterioration of flame retardant properties. On the other hand, without titanate coupling treatment, the interfacial bonding between the filler and the rubber matrix was weak, and the stress transfer efficiency was low, leading to a significant decrease in mechanical properties. The results in the table confirm the necessity of constructing a core-shell structure and surface organic modification to improve the overall performance of the filler.

[0043] The mechanical properties and abrasion resistance of the sample in Comparative Example 2 are between those of Comparative Example 1 and Example 1. Its thermal stability also shows the same trend. This may be because only magnesium phytate coating is performed and the titanate coupling in step S2 is omitted. Although the magnesium phytate coating layer improves the thermal stability of the filler to some extent, the lack of a molecular bridging interface constructed by the coupling agent results in insufficient compatibility between the filler and the rubber. Under dynamic load, interfacial slippage is likely to occur, leading to a decrease in abrasion resistance and tear resistance.

[0044] The tear strength and limiting oxygen index of the sample in Comparative Example 3 were significantly lower than those in Example 1, and the abrasion loss was higher. This may be because silane-modified mica powder was not added in step S4, resulting in the lack of synergistic reinforcement from the lamellar filler. The lamellar structure of mica powder can effectively extend the stress transmission path and improve tear resistance. Its barrier effect also helps to delay thermal and oxygen diffusion. In Comparative Example 3, the reinforcement effect relied solely on the main filler, failing to form a multi-dimensional reinforcing network, leading to insufficient durability of the material under harsh working conditions.

[0045] The hardness, tensile strength, and tear strength of the sample in Comparative Example 4 were significantly lower than those in the Example, and also lower than those in Comparative Examples 2 and 3. This may be because the lack of a magnesium phytate coating layer on the brucite caused early thermal decomposition of the brucite at high temperatures, which in turn damaged the integrity of the filler structure and prevented it from effectively transferring stress. Therefore, even with the introduction of titanate coupling agent and mica powder, it was difficult to construct a stable synergistic reinforcing network. This result conversely proves that the magnesium phytate coating layer is an indispensable cornerstone for the formation of the ternary synergistic system.

[0046] It should be noted that, in this document, terms such as “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0047] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention.

Claims

1. A method for preparing a magnesium-based high-temperature resistant filler for rubber conveyor belts, characterized in that, Prepared by the following steps: Step 1: Using the co-precipitation method, with brucite powder as the matrix core, phytic acid as the organic phosphorus source, and magnesium chloride as the magnesium source, the uniform coating of magnesium phytate is achieved through in-situ deposition to obtain magnesium phytate@brucite composite powder. Step 2: Using TTS-toluene solution as a modifier, titanate coupling agent molecules are chemically bonded to the surface of magnesium phytate@brucite composite powder to obtain titanate-esterified magnesium phytate@brucite composite powder. Step 3: The titanate-modified magnesium phytate@magnesium hydroxide composite powder is mixed with silane-modified mica powder by high-speed mechanical mixing to obtain magnesium-based high-temperature resistant filler for rubber conveyor belts. The mass ratio of the titanate-modified magnesium phytate@magnesium hydroxide composite powder to the silane-modified mica powder is 50-70g: 3-6g. The silane-modified mica powder is mica powder modified with hexadecyltrimethoxysilane or octadecyltrimethoxysilane.

2. The method for preparing a magnesium-based high-temperature resistant filler for rubber conveyor belts according to claim 1, characterized in that, The specific preparation steps for the magnesium-based high-temperature resistant filler used in rubber conveyor belts are as follows: Titanate-modified magnesium phytate@magnesium hydroxide composite powder and silane-modified mica powder were placed in a high-speed mixer and mixed at 500-800 r / min for 10-15 min at room temperature. Then, the mixture was mixed at 1000-1500 r / min for 15-25 min. The mixture was then dried in an air-drying environment at 75-85℃ for 1-2 h. Finally, it was passed through a 150-200 mesh sieve to obtain magnesium-based high-temperature resistant filler for rubber conveyor belts.

3. The method for preparing a magnesium-based high-temperature resistant filler for rubber conveyor belts according to claim 2, characterized in that, The specific preparation steps of the titanate-esterified magnesium phytate@brucite composite powder are as follows: Tristearoyloxyisopropyl titanate was dissolved in toluene and stirred until completely dissolved to prepare a coupling agent solution, which was then transferred to a sprayer for later use. Magnesium phytate@brucite composite powder was added to a reaction vessel and preheated and stirred at 65-75℃ and 200-400 r / min for 20-30 min. The coupling agent solution was then slowly and evenly sprayed into the reaction vessel through a sprayer. After spraying, the reaction vessel was sealed and reacted at 300-500 r / min and 65-75℃ for 50-70 min. After the reaction was completed, the powder product was vacuum dried at 75-85℃ for 2-3 h to finally obtain titanate-esterified magnesium phytate@brucite composite powder.

4. The method for preparing a magnesium-based high-temperature resistant filler for rubber conveyor belts according to claim 3, characterized in that, The ratio of the tristearoyloxyisopropyl titanate, toluene, magnesium phytate@brucite composite powder is 1.5-2.4g: 20-30mL: 50-70g.

5. The method for preparing a magnesium-based high-temperature resistant filler for a rubber conveyor belt according to claim 3, characterized in that, The specific preparation steps of the magnesium phytate@brucite composite powder are as follows: A 58.7% phytic acid solution was added to a reaction vessel, and a 5-10% ammonia solution was slowly added dropwise to adjust the pH of the system to 6.5-7.

5. A magnesium hydroxide suspension was then added to the reaction vessel, and the mixture was stirred at 300-600 r / min at room temperature. Magnesium chloride solution was then slowly added dropwise to the reaction vessel at a rate of 1-2 drops / s. The mixture was stirred at a constant temperature for 1-1.5 h. After the reaction was completed, the product was washed with deionized water until the filtrate was neutral. The product was then filtered, and the filter cake was dried at 75-85℃ for 4-6 h. Finally, the dried block product was ground and passed through a 150-200 mesh standard sieve to obtain magnesium phytate@magnesium hydroxide composite powder.

6. The method for preparing a magnesium-based high-temperature resistant filler for a rubber conveyor belt according to claim 5, characterized in that, The brucite suspension is prepared by stirring 80-120g of brucite powder and 1-2.5L of deionized water at room temperature at a speed of 200-500r / min for 10-30min.

7. The method for preparing a magnesium-based high-temperature resistant filler for rubber conveyor belts according to claim 5, characterized in that, The magnesium chloride solution consists of 14-26g of magnesium chloride hexahydrate and 80-150mL of deionized water.

8. The method for preparing a magnesium-based high-temperature resistant filler for a rubber conveyor belt according to claim 5, characterized in that, The mass ratio of the brucite powder, magnesium chloride hexahydrate, and phytic acid compounds is 80-120g: 14-26g: 16-22g.

9. A magnesium-based high-temperature resistant filler for rubber conveyor belts, characterized in that, It is prepared by the preparation method described in any one of claims 1-8.

Citation Information

Patent Citations

  • Preparation method for heat-conduction filling material applied to PVC(polyvinyl chloride) / PE(polyethylene) plastic

    CN110183797A

  • Talcum powder-magnesium hydroxide composite inorganic flame-retardant filler and preparation method thereof

    CN111793248A